2020
DOI: 10.3846/enviro.2020.683
|View full text |Cite
|
Sign up to set email alerts
|

Rural Road Reverse Engineering Using Bim: An Italian Case Study

Abstract: The use of Building Information Modeling (BIM) is changing the way to perceive, manage and maintain any infrastructural project. The concept of Smart Roads relaunches the transport infrastructure sector through the digital transformation, able to create lean, quality, safer and cheaper infrastructures. The reverse engineering parametric modeling process was applied to “SS18 VAR” rural road, one of the main viabilities in Southern Italy. The case study was developed in according to the following steps:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Such features may be replaced by those supplied by the manufacturer when the real works are performed. Moreover, in both OpenRoads ConceptStation and OpenRoads Designer, it has been possible to incorporate the elements with their attributes on the program library [41]. In addition, a new table indicating element to element any aspect associated with any specific traffic sign including its location or other aspects of the construction works was included.…”
Section: Discussionmentioning
confidence: 99%
“…Such features may be replaced by those supplied by the manufacturer when the real works are performed. Moreover, in both OpenRoads ConceptStation and OpenRoads Designer, it has been possible to incorporate the elements with their attributes on the program library [41]. In addition, a new table indicating element to element any aspect associated with any specific traffic sign including its location or other aspects of the construction works was included.…”
Section: Discussionmentioning
confidence: 99%
“…The research presented in [27] investigates the reconstruction projects using statistical analysis, multicriteria decision-making methods and application of BIM methodology. A case study of transport infrastructure in the Southern Italy region is presented in [28]. In this study, the parametric modelling method was used in reverse engineering.…”
Section: Bim In Transport Infrastructurementioning
confidence: 99%
“…The possibility offered by BIM as a tool for digitizing buildings and the information related to their functionality is widely established (Liu et al, 2019). Indeed, there are several case studies related to the realization of as-built models of historical buildings (Lopez et al, 2018) that have confirmed the validity of this methodology for the realization of back-analysis and reverse-engineering workflows (Adekunle et al, 2022;Abbondati et al, 2020). Yet, few studies focus on roads of historical and/or archaeological character, and they are often limited to particular works of art (bridges, aqueducts, etc.)…”
Section: Research Motivation and Objectivesmentioning
confidence: 99%